Socialization of Personal Financial Management through Basic Accounting Principles among Santriwati Islamic Boarding School Griya Santri Mahabbah - Dinda Safira; Ananda Meilani; Wulan Oktaviani; Hendri Hermawan Adinugraha; Ria Anisatus Sholihah; Dliyaudin Achmad (Pengabdian: Jurnal Abdimas, 2023)
Background. Santriwati who are pursuing college education have unique needs and challenges in managing their personal finances. With socialization about financial management, they will realize the consequences of unwise financial decisions and the importance of managing finances well to achieve financial stability in the future. Purpose. The purpose of this community service activity is to provide knowledge about personal financial management based on the basics of accounting for female students at the Griya Santri Mahabbah Islamic Boarding School. This service activity also encourages female students of the Griya Santri Mahabbah Islamic Boarding School to get used to managing personal finances Method. The research method used is the socialization method. The implementation of this service is carried out through three stages: service planning, service implementation, and service evaluation. Results. 10 out of 12 people will try to apply accounting financial records to personal financial management. They will try to keep records of income and expenses for certain periods of their daily lives. As for the two people who don't understand, they haven't tried this financial management, so they can't apply accounting financial records. Conclusion. The socialization activities regarding personal financial management that were carried out at the Griya Santri Mahabbah Islamic Boarding School were carried out smoothly according to plan and even received enthusiasm and a good response from the female students. This socialization activity was carried out to provide information to female students who still had difficulty managing finances. In the future, it is hoped that the community service activities that are currently being carried out can be continued with ongoing activities in the coming year and added material on more in-depth financial management. So that knowledge about financial management can be understood and used as capital for the future of female students in managing better financial planning.